(untitled) (Analytic Teaching, 1988)
Introduction: The evaluation of instructional programs designed to teach thinking skills has many important educational implications for school children, classroom teachers, school administrators and society as a whole. Many educators (e.g., Bloom, 1987; Presseisen, 1987; Nisbett, et al., 1987; Sternberg, 1985; Beyer, 1984) as well as several popular writers (e.g., Naisbitt, 1982; Toffler, 1980) suggest that, at the least, education must teach reasoning, critical analysis, and problem solving to the citizens of the 21st century. In fact, Costa (1987) goes so far as to propose that the ability to think is a prerequisite to the "basis" or the basic of the basics.